Enhancing Student Academic Writing : Developing a Booklet of Instructional Activities and Strategies to Support Lecturers to Teach Writing in the Context of Their Disciplines. - Radloff, Alex; de la Harpe, Barbara (Committee for University Teaching and Staff Development, 2000)
This is a final report for a 1998 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The project aimed to improve university student academic writing through production of a booklet of instructional activities and strategies for lecturers. The report summarises the project aims and outcomes and provides justification and educational rationale for its development. Evaluation of the project is discussed in detail.